Genitourinary syndrome in women at the Dr. Cosme Ordoñez Carceller university polyclinic, Cuba - Maure-Barcia, Javier; Jorna Calixto, Ana Rosa; Véliz-Martínez, Pedro Luís (Horizonte Sanitario, 2023)
Objective: To determine the frequency and intensity of genitourinary syndrome of menopause in womens treated in the climacteric and menopause consultation of the University Polyclinic ’Dr. Cosme Ordonez Carceller. Methods: Observational, descriptive and cross-sectional research, carried out in the period between January 2018 and December 2022. The universe of work was made up of 2962 middle-aged women from the Dr. Cosme Ordoñez Carceller university polyclinic. The sample consisted of 353 women selected by simple stratified sampling. For data collection, a Clinical History model was used, from which aspects related to sociodemographic data were extracted, the age of onset of climacteric symptoms and menopause, genitourinary disorders and their intensity in relation to the stage of climacteric syndrome. Results: The average age of the women studied was 49.4 +/- 5.18 years. The largest number of them were in perimenopause (60.1%), while the percentage in postmenopausal women reached 39.9%. The mean age of onset of symptoms was 45.8 +/- 6.2 years, the highest frequency occurring between 45 and 49 years (61.5%). The average age of onset of menopause of 48.4+/- 3.7 years, which represents that more than two thirds (81.6%) of the women had their last menstruation over 45 years of age. Genitourinary alterations predominated in perimenopause and mild intensity. Conclusions: The genitourinary syndrome of menopause constitutes a group of frequent clinical manifestations in women in the climacteric stage and affect more than two thirds of the women al the policlinic, appearing more frequently between the ages of 45 and 49, in perimenopause and with mild intensity. Key words: Climacteric; Menopause; Prolapse; Cystocele; Rectocele.